The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00232-005-7008-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of Steady-State Laurdan Fluorescence to Detect Changes in Liquid Ordered Phases in Human Erythrocyte Membranes

Abstract: In artificial phospholipid bilayers, dual measurements of laurdan steady-state anisotropy and emission spectra can be used to identify the presence of liquid ordered phases. Human erythrocytes were used as a model to test whether similar measurements could be applied to biological samples. Specifically, laurdan anisotropy and emission spectra were obtained from native erythrocytes before and after treatment with calcium ionophore and from the microvesicles (known to be enriched in liquid ordered domains) shed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…This tendency is consistent with phytosterol depletion, according to a temperaturedependence study of TMA-DPH fluorescence anisotropy in DPPC-sterol vesicles (48). Indeed, anisotropy values reflect both structural (order) and dynamic (fluidity) membrane properties (29,42), whereas only structural consequences, (i.e., decreased acyl chain order) are expected from sterol depletion. The Laurdan GPex temperature profiles were, on the contrary, highly influenced by M␤CD treatment.…”
Section: Phytosterols Modulate Plant Pm Lateral Organizationsupporting
confidence: 79%
“…This tendency is consistent with phytosterol depletion, according to a temperaturedependence study of TMA-DPH fluorescence anisotropy in DPPC-sterol vesicles (48). Indeed, anisotropy values reflect both structural (order) and dynamic (fluidity) membrane properties (29,42), whereas only structural consequences, (i.e., decreased acyl chain order) are expected from sterol depletion. The Laurdan GPex temperature profiles were, on the contrary, highly influenced by M␤CD treatment.…”
Section: Phytosterols Modulate Plant Pm Lateral Organizationsupporting
confidence: 79%
“…A higher value of fl uorescence anisotropy can refl ect lower membrane fl uidity and higher structural order of the cell membrane (Vest et al 2006, Marczak 2009). Several researchers found that MG63 cells exposed at 0.4 T had signifi cantly increased cell membrane rigidity, with an increased related ratio of about 15% (Chiu et al 2007, Lin et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To allow the DPH to integrate into the bilayer, the mixture was incubated at 65°C for 1 hour. Anisotropy measurements were obtained as previously described [25]. Briefly, DPH was excited at 350 nm and the fluorescence detected at 430 nm.…”
Section: Methodsmentioning
confidence: 99%